Training on Using and Making Cloth Masks for Housewives in Kerinjing Village - Bashir, Abdul; Muhyiddin, Nurlina T; Syamsurijal, Syamsurijal; Susetyo, Didik; Soebyakto, Bambang Bemby; Hamira, Hamira; Astria, Andi Nurul (Sricommerce: Journal of Sriwijaya Community Services, 2021)
The spread of the Covid-19 outbreak is a serious problem that threatens the health and must be addressed immediately. People are required to comply with health protocols, one of which is by wearing a mask. The use of masks is an effort to minimize the transmission of the Covid-19 virus. The high demand for masks, especially medical masks, causes scarcity and high prices in the market. As an alternative, a cloth mask is needed that can be used daily for activities for the community during the Covid-19 pandemic. The purpose of this community service activity is to socialize the proper and correct use of cloth masks. This service activity also aims to provide training to housewives to make masks independently from cloth that can be used in daily activities. Besides functioning as a prevention for the Covid-19 virus, cloth masks can also be sold as an effort for housewives during the Covid-19 pandemic. Methods of activity and implementation are carried out through outreach, training, and mentoring approaches.